Guanosina modula a funcionalidade e a bioenergética mitocondrial em ratos - Courtes, Aline Alves (2019)
Mitochondrial dysfunction is associated with a wide variety of degenerative and metabolic diseases, cancer and aging. All these clinical manifestations result from problems in the mitochondria in playing their central role of bioenergetics in cellular biology. Mitochondrial bioenergetics and redox status are also determined by intracellular levels of calcium (Ca 2+ ). The Ca 2+ mitochondrial regulates the energy metabolism, however in high concentrations, stimulates the cell death pathways through the mitochondria. Mitochondria are sensitive to changes in the physiological state of the cells and appear to play a critical role in secondary injury that occurs after traumatic brain injury (TBI). Therapeutic agents with neuroprotective properties may help in the understanding of disorders related to mitochondrial dysfunctions and allow new perspectives for their application. In this context, the nucleoside guanosine, an endogenous molecule member of the purinergic system, has been studied in different experimental models, since it demonstrates a neuroprotective effect due to modulation of the glutamatergic system and maintenance of the redox system. Thus, the present thesis aimed to evaluate guanosine effects on changes in mitochondrial bioenergetic functionality in rats, through an in vitro study against calcium-induced damage, and in vivo, against damage caused by mild TBI. The results presented in the in vitro study showed that guanosine presented a protective effect against mitochondrial dysfunction induced by Ca 2+ imbalance, since it reduced mitochondrial swelling in the presence of Ca 2+ , decreased levels of reactive oxygen species (ROS), hydrogen peroxide (H2O2), increased the activity of the enzyme Mn- superoxide dismutase, oxidative phosphorylation and tricarboxylic acid cycle activity. Our findings from in vivo study showed that a single dose of guanosine injected intraperitoneally 2 hours after a mild TBI in rats increased oxidative phosphorylation, the electron transport system in the presence of a uncoupler and the ratio of respiratory control in the cortex and hippocampus, evaluated through high-resolution respirometry. Guanosine also protected against locomotor, exploratory and short-term memory deficits induced by the TBI 24 hours after the injury. Thus, we demonstrate that guanosine has a protective effect in reducing Ca 2+ - induced mitochondrial damage and that these effects were not associated with its direct antioxidant properties per se or stabilization of the mitochondrial membrane potential. It can be considered as a strategy to protect against neurological damage in pathologies associated with the central nervous system as well as in mitochondrial disorders, making this molecule a therapeutic attraction for the treatment of TBI.